Diffusion and benefits evaluation of electric vehicles under policy interventions based on a multiagent system dynamics model. (1st March 2022) - Li, Jingjing; Nian, Victor; Jiao, Jianling
Highlights: A multiagent system dynamics model is established. The impact of different policies on the diffusion and benefits of EVs is studied. EV diffusion is most significantly impacted by licence plate restrictions. The health benefits of EVs are the greatest. The benefits of government subsidies are positive. Abstract: Electric vehicle (EV) diffusion plays a vital role in transforming and upgrading China's automobile industry by ensuring energy security, improving air quality, and contributing to achieving the goal of carbon neutrality by 2060. EV diffusion is a complex dynamic system that involves various agent interactions. Nevertheless, previous research has rarely focused on the impact of different policies on EV diffusion under multiagent interactions and thus has not systematically evaluated its diffusion benefits. This paper establishes a multiagent system dynamics (SD) model to explore the impact of different policies on the diffusion and benefits of EVs. The results indicate that (1) EV diffusion is most significantly impacted by licence plate restrictions, following by charging pile construction subsidy, most sensitive to purchase subsidy policies, and least affected by government R&D subsidies. (2) Moreover, all four policies decrease EV energy benefits but positively impact the carbon emission reduction, health, and social benefits of EVs. The health benefits of EVs are the greatest, followed by the carbon emission reduction benefits. (3) The benefits of government subsidies to EV manufacturers, consumers, and charging infrastructure operators are positive. Finally, by integrating the development situation of China's EV industry, feasible policy suggestions are proposed for sustainable development.